Course Design For Esp Students (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article presents an initial outline for an English for Specific Purposes (ESP) project focusing on English for Dentists, emphasizing the importance of effective communication skills in the dental field. The course aims to address the specific language needs of dental professionals, improve patient care, and facilitate professional connections within the industry. The course context, duration, participants, language skills to be developed, and selected ESP course example are outlined, with a focus on adapting materials and methodologies for the English for Dentists course. The Language in the Workplace course by Catherine Nickerson serves as a model for designing effective communication skills development in the dental profession.This project aims to enhance the communication abilities of dental professionals, improve patient care, and facilitate professional connections within the dental industry.